A partial compensation scheme for MMC-based railway cophase power supply. Issue 4 (25th August 2020) - Sun, Peiliang; Li, Kang; Xing, Chen
Abstract: This paper presents a partial compensation scheme for V/v transformer cophase traction power supply in high-speed railway systems. The scheme compensates variable traction load current, and controls the current phase at the secondary side of the V/v transformer for power factor correction and negative sequence current reduction. To achieve this, the grid side current phase angles are optimized while satisfying the grid code on the power factor and voltage unbalance limits. The optimized phase angles are then used to design control references under varying load conditions. The compensation control action is updated regularly based on real-time measurements of the traction load, and the required currents are controlled by a 25-level single-phase back-to-back MMC power conditioner to achieve the compensation target. Static and dynamic load compensation performances are verified based on the simulation studies.